2014
DOI: 10.1002/cssc.201402373
|View full text |Cite
|
Sign up to set email alerts
|

Aminosilanes Grafted to Basic Alumina as CO2 Adsorbents—Role of Grafting Conditions on CO2 Adsorption Properties

Abstract: Solid oxide-supported amine sorbents for CO2 capture are amongst the most rapidly developing classes of sorbent materials for CO2 capture. Herein, basic γ supports are used as hosts for amine sites through the grafting of 3-aminopropyltrimethoxysilane to the alumina surface under a variety of conditions, yielding the expected surface-grafted alkylamine groups, as demonstrated by FTIR spectroscopy and (29)Si and (13)C cross-polarization magic-angle spinning (CPMAS NMR) spectroscopy. Grafting amine sites on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
64
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 38 publications
(71 citation statements)
references
References 114 publications
(276 reference statements)
7
64
0
Order By: Relevance
“…This indicates large mesopores are present in these materials (Figure 2a). [15] We further note that the values for the amine density differed betweent he two samples, with the D-Al 2 O 3 series showingg enerally lower values. As imilar trend was observed for the D-Al 2 O 3 series (Figure 2b), again suggesting the APS is being deposited inside the mesopores of these materials instead of purely on the exterior surface of the supports.…”
Section: Resultsmentioning
confidence: 66%
See 4 more Smart Citations
“…This indicates large mesopores are present in these materials (Figure 2a). [15] We further note that the values for the amine density differed betweent he two samples, with the D-Al 2 O 3 series showingg enerally lower values. As imilar trend was observed for the D-Al 2 O 3 series (Figure 2b), again suggesting the APS is being deposited inside the mesopores of these materials instead of purely on the exterior surface of the supports.…”
Section: Resultsmentioning
confidence: 66%
“…[15,17,52] The pattern was less crystalline than is typicallyo bserved for commercial g-alumina, which may be owed to the templated mesoporosity in the sample. The pattern for the ordered alumina sample demonstrated that it had crystallinity and was in good agreement with patternsi nt he literature, exclusively showing peaks associated with the cubic Fd3m space group of g-alumina.…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations